INFLUENCE OF OLEIC ACID ON THE IN VITRO PENETRATION OF DICLOFENAC SODIUM GEL - Lidya Ameliana; Esti Hendradi; Mochammad Yuwono (UPT Penerbitan Universitas Jember)
Diclofenac sodium (DS) is a nonsteroidalantiinflammatory drugs (NSAIDs), that inhibitscyclooxygenase-2 enzyme (COX-2). It has first passmetabolism by 40-50%, because of its shortbiological half-life, the drug has to be givenfrequently (Ganiswara, 2005). Dose of DS in gel is 1%(Sweetman, 2007). In peroral use, it may cause therisk of gastrointestinal bleeding, cardiovascular,hypersensitivity reactions and disorders of thecentral nervous (Katzung, 2002, Chuasuwan, et al.,2008).DS does not penetrate well through skin and cannotreach the effective concentration at the site ofaction after transdermal application (Mohammed,2001; Ozguney, et al., 2006). DS partition coefficientin n-octanol-buffer aqua (log P) was 1.1 (Chuasuwan,2008). Lipophilic nature of the stratum corneum andthe hydrophilic nature of the underlying tissuesshowed that the drug will penetrate the skin shouldhave an optimal balance between the lipophilic andhydrophilic properties. In general, the skin is morepermeable to the material which has a partitioncoefficient (P) in octanol-water between 10-1000(Michniac-Kohn et al., 2005).Oleic acid enhances the penetration of drugs intothe skin by increasing the fluidity of the stratumcorneum lipids through the establishment ofchannels (water channels) (Fang , et al , 2003)This study aimed to know the influence of OleicAcid (OA) in several concentrations (1%, 3% and5%) as penetration enhancer on the in vitropenetration of topical DS gel. Furthermore, thephysical properties of the topical preparation(organoleptic, pH and viscosity), and DS penetrationpercutaneously through rat skin . Then observedthat in spite of DS assay and penetrate through therat skin at certain intervals and observed by meansof HPLC.